Pripovedovalec, fokalizacija in avtorjev glas v krajših pripovedih Draga Jančarja - Štuhec, Miran (Slavistična revija, 2005)
The first goal of the paper is to define the narrative structure of Jančar's short prose and novellas, or, rather, recognize the mechanism invariantly working in individual texts. The second goal focuses on the signals that through author's voice, selected vocabulary, and the poetics of the view permeate individual works from the corpus.
Keywords: Jančar, Drago, 1948-; kratka proza; literarna teorija; literary theory; pripovedovalec; Slovene literature; slovenska književnost